Spatial planning for sustainable development in Malaysia: current practice and challenges - Shuid, Syafiee (2023)
Describing current Development Plan System in Malaysia and challenges of urban development. How the development plan prepared in line with SDGs and other national economic plan. Role played by Malaysian Institute of Planners (MIP) and Board of Town Planners (BTP) in ensuring quality and competent urban planners to prepare development plans. To discuss the future of development plan and spatial planning in particular.